1999
DOI: 10.1007/s002560050519
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell chondrosarcoma of the pelvis in a skeletally immature patient

Abstract: We report on a case of clear cell chondrosarcoma (CCCS) of the left iliac bone in a 12-year-old skeletally immature boy. Radiographic examination revealed an aggressive osteolytic lesion with areas of mineralization. Fluid-fluid levels were seen on T2-weighted MR images. Laboratory data showed slight elevation of serum alkaline phosphatase. The biopsy specimen showed histological features of CCCS with some resemblance to osteosarcoma, such as prominent irregular osteoid formation among clear tumor cells. Surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…b Axial T2W FSE (TE 160, TR 5,500) image demonstrates that the signal in the superior layer is now high (black arrow and the inferior layer is low (white arrow) Table 2 The prevalence of The presence of the L/H SI pattern on T1W images is significantly contributed to by lesions that are primary ABC (n=24/50) or contain secondary ABC change (21/50). Secondary ABC formation can occur in SBC [23], fibrous dysplasia [21], GCT [1,18], osteosarcoma, may be relatively frequent in chondroblastoma (4/5 cases [11]),and rarely in clear cell chondrosarcoma [42]. Such lesions are relatively frequent in this group: SBC, n=4; chondroblastoma, n=6; GCT, n=5; osteosarcoma, n=6.…”
Section: Discussionmentioning
confidence: 93%
“…b Axial T2W FSE (TE 160, TR 5,500) image demonstrates that the signal in the superior layer is now high (black arrow and the inferior layer is low (white arrow) Table 2 The prevalence of The presence of the L/H SI pattern on T1W images is significantly contributed to by lesions that are primary ABC (n=24/50) or contain secondary ABC change (21/50). Secondary ABC formation can occur in SBC [23], fibrous dysplasia [21], GCT [1,18], osteosarcoma, may be relatively frequent in chondroblastoma (4/5 cases [11]),and rarely in clear cell chondrosarcoma [42]. Such lesions are relatively frequent in this group: SBC, n=4; chondroblastoma, n=6; GCT, n=5; osteosarcoma, n=6.…”
Section: Discussionmentioning
confidence: 93%
“…The youngest patient in a series of 47 cases from the Mayo Clinic was 14 years of age [3]. In a review of the English language literature, the youngest reported case of a CCCS occurred in the pelvis of a skeletally immature 12-year-old boy in Japan [8]. No other reports of CCCS occurring in skeletally immature individuals were found.…”
Section: Case Reportmentioning
confidence: 99%
“…However, CCCS most commonly occurs in the third to fifth decade, whereas chondroblastoma occurs in the first and second decades [3,12]. The previously published case in a 12-year-old boy occurred in the pelvis, not the classic epiphyseal location [8]. Thus, CCCS has not traditionally been included in the differential diagnosis of epiphyseal lesions in skeletally immature patients.…”
Section: Case Reportmentioning
confidence: 99%
“…[7]199944 × LGN/AN/AN/AIshida et al. [45]199911 × LGNED11R000Nathan et al. [46]19991N/AN/AN/AN/AAyoub at al.…”
Section: Resultsmentioning
confidence: 99%